Retained textiloma after elective cesarean section - Suárez-Torres, Ismael (2017)
Retained surgical swab or textiloma is an infrequent but avoidable result of surgical error. The reported incidence is 1 in 1 000 to 15 000 intraabdominal surgeries. A retained surgical swab may cause serious complications and may lead to death. We present the case of a 26 year-old woman who was seen for abdominal pain. Her surgical history included a cesarean section 20 months ago. During laparotomy, a retained surgical sponge located 25 centimeters from the ileocecal valve was found and resected en bloc. Although rare in daily practice, a retained intraperitoneal swab body should be considered in patients with complex abdominal symptoms following a history of abdominal surgery.